Subsurface phase imaging of tapping‐mode atomic force microscopy at phase resonance. (23rd July 2022) - Sun, Baishun; Cao, Liang; Xie, Chenchen; Lu, Zhengcheng; Liu, Mengnan; Yu, Miao; Song, Zhengxun; Wen, Zhankun; Wang, Zuobin
Abstract: The phase image of tapping‐mode atomic force microscopy (TM‐AFM) contains energy dissipation, which is related to the sample information on the physical properties such as the sample Young's modulus, adhesion, surface morphology and subsurface morphology. When TM‐AFM is used for sample measurement, the frequency near the first resonance peak of probe is usually selected to drive the probe vibration. When the probe vibration is driven by the frequency, the probe has a high amplitude sensitivity, but the phase sensitivity is relatively low. In this paper, the frequency at the probe phase resonance peak was selected for driving the probe vibration to measure the sample, which improved the image resolution. Phase imaging was performed on three uniform photoresist samples with different thicknesses and the same structure. When the scanning parameters were fixed and the probe setpoint value was changed alone, it was found that with the decrease of setpoint value the horizontal resolution of the phase subsurface image was decreased, and the depth sensitivity was increased first and then decreased. The result shows that TM‐AFM working at the phase resonance peak can better realise the subsurface imaging of samples at different depths. Phase subsurface imaging at the resonance can be used to quantitatively obtain subsurface phase images of different depths.